Improved soft clay characteristics due to stone column installation - Guetif, Z.; Bouassida, M.; Debats, J.M. (Computers and geotechnics, 2007)
A method is proposed for evaluating the improvement of the Young modulus of soft clay in which a vibrocompacted stone column is installed. By considering a composite cell model a numerical analysis is carried out using Plaxis software to simulate the vibrocompaction technique, which leads to a form of primary consolidation of the soft clay. For the numerical simulation Mohr Coulomb perfect plastic behaviour is considered for the improved soil constituents. From numerical results the degree of improvement of the Young modulus soft clay has been estimated. Also, the zone of influence of the improved soft clay has been predicted.